2014
DOI: 10.1038/bjc.2014.403
|View full text |Cite
|
Sign up to set email alerts
|

TMPRSS4: an emerging potential therapeutic target in cancer

Abstract: Altered expression and activity of proteases is a key event in cancer, particularly in relation to invasion, modification of the extracellular matrix and metastasis. The transmembrane protease, serine 4 (TMPRSS4) is closely related to other cancer-associated proteases, such as hepsin, TMPRSS2 and matriptase. We review in this study up-to-date information about expression, role, regulation and clinical relevance of TMPRSS4 in cancer. Increased expression of this protease is associated with acquisition of epithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
57
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(60 citation statements)
references
References 29 publications
3
57
0
Order By: Relevance
“…Expression of the serine protease TMPRSS4 is highly increased in a variety of solid tumors and is associated with poor prognosis in some cancer types such as breast, colon, cervix, thyroid and liver [8, 11]. Our present study shows for the first time that TMPRSS4 is an independent prognostic indicator of reduced survival in patients with squamous NSCLC at early stages, thus validating our previous findings by mRNA analysis [7].…”
Section: Discussionsupporting
confidence: 89%
“…Expression of the serine protease TMPRSS4 is highly increased in a variety of solid tumors and is associated with poor prognosis in some cancer types such as breast, colon, cervix, thyroid and liver [8, 11]. Our present study shows for the first time that TMPRSS4 is an independent prognostic indicator of reduced survival in patients with squamous NSCLC at early stages, thus validating our previous findings by mRNA analysis [7].…”
Section: Discussionsupporting
confidence: 89%
“…TMPRSS4 could be a useful prognostic biomarker or a promising therapeutic target for solid tumors [1]. However, further studies analyzing specific tumor types and perspectives are needed to further verify the clinical significance of TMPRSS4 expression in solid tumors.…”
Section: Discussionmentioning
confidence: 99%
“…It has been implied that TMPRSS4 could be an emerging potential therapeutic target in cancer [1]. ITMPRSS4 reduced migration and invasion of lung and colon cancer cells [9, 14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, increases in markers for cancer stem cells (CSCs) such as aldehyde dehydrogenase (ALDH) and octamer-binding transcription factor 4 (OCT-4) are strongly positively correlated with TMPRSS4 expression (de Aberasturi et al, 2016). Several reports have suggested that TMPRSS4 associates with poor prognosis and survival in a variety of different cancers (Cheng et al, 2013a,b; Wu et al, 2014; de Aberasturi and Calvo, 2015; Wang et al, 2015), which may be a result of an increase in the CSCs population, although the factors leading to TMPRSS4 upregulation are still not identified. One recent finding suggests that increased TMPRSS4 in cancer may result from gene-silencing of tissue factor pathway inhibitor 2 (TFPI-2), a consequence of improper methylation (Hamamoto et al, 2015).…”
Section: Tmprss2 and Tmprss4mentioning
confidence: 99%